Navigating the gig economy: exploring challenges and motivations for the wellbeing of Gen Y and Gen Z gig workers - Jikku Susan Kurian; N. Bindu Madhavi (Cogent Psychology)
Objective Gig work, also known as short-term, contract work and non-traditional work has shaped gig economy, however, the research related to gig workers needs further exploration. This empirical study explores the motivations, challenges, quality of life, stress and well-being of gig workers.Method Drawing from previous literature a conceptual framework was created. A quantitative approach involving 347 gig workers was employed to conduct this study. A structured interview was used to identify the motivations, challenges, stress, quality of life and well-being of gig workers involved in different gig work such as car driving, salon service or item delivery service. The collected data was analyzed using AMOS software.Results It was noted that motivation positively impacts quality of life and has a positive effect on well-being of gig workers. On the contrary, challenges have a negative influence on stress and a subsequent negative effect on well-being. Further, stress and quality of life had a mediating role and gig workers attributes moderated the relationship of well-being with motivations and challenges.Conclusion Based on the outcome, gig work characteristics can be modified, and management practices can be improved to motivate gig workers, reduce the challenges and to improve their wellbeing.